Renewable energy : problems and prospects in Coachella Valley, California - Pick, James B. (Springer, 2017)
The book analyzes the problems and potential of renewable energy development for the Coachella Valley of California and provides a useful case study for renewable energy feasibility assessments for other areas. A conceptual model, Integrated Policy Assessment Theory for Renewable Energy, is given and justified for renewable energy development in the Valley. Further, Central Place Theory, well known in urban geography, is discussed and it is seen to be very relevant to the understanding the Coachella Valley?s city sizes and renewable energy markets, compared to the greater Los Angeles region. The book?s research methods include geospatial mapping and analysis and interviews leaders in small innovative firms, government agencies, and nonprofits. The many findings of the book include evaluation of how the Valley?s socioeconomic and transportation features influence renewable energy development, the scope of markets for solar and wind energy in the Valley, spatial confluences of renewable energy facilities with other features, and the future potential of ground-source heat pumps. Benchmark comparison of the Coachella Valley is done with two leading wind and solar regions elsewhere in the country, to assess the Valley?s evolution and opportunities in renewable energy. The book concludes by evaluating the prospects and problems for the growth of renewable entrepreneurship, manufacturing, assembly, and operations in Coachella Valley. This leads to policy recommendations grounded in the book?s research findings, which are intended for use by governments, businesses, and nonprofits. The hope is that many of the developmental experiences from the Coachella Valley will be helpful not only within the Valley but to other communities nationwide and worldwide.
Keywords: Renewable energy sources -- California -- Coachella Valley.; California -- Coachella Valley.; elektronické knihy; electronic books